Phylogenetic Study of Dioecious and Parthenogenetic Populations of Canthocamptus staphylinus (Crustacea, Copepoda, Harpacticoida) - Elena Kochanova; Jouko Sarvala; Elena Fefilova (Southern California Academy of Sciences, 2022)
The phylogenetic relationships of four dioecious populations and one parthenogenetic population of the harpacticoid Canthocamptus staphylinus Jurine were studied. Analysis of the mtCOI gene revealed two main clades as a phylogenetic tree and a network of haplotypes: a clade with Fennoscandian populations in Lake Pääjärvi (Finland) and Lake Vänern (Sweden), and a second clade with populations in Lake Võrtsjärv (Estonia), Orlov Pond in Saint Petersburg (Russia), and the type locality of the species in Lake Geneva (Switzerland).The parthenogenetic population of C. staphylinus showed the smallest nucleotide and haplotype polymorphisms and could have evolved as a reaction to the changing environmental conditions following the Last Glacial Maximum, 20K YBP.